SCHOOL ADMINISTRATORS' ROLES AFFECTING THE STUDENT ASSISTANCE SYSTEM OPERATION IN SCHOOLS UNDER CHACHOENGSAO PRIMARY EDUCATIONAL SERVICE AREA OFFICE 1 - Phetra, Naramon; Narkpoy, Linda; Onkasem, Porntip (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The objectives of this research were to: 1) examine the level of school administrators’ roles, 2) explore the level of the student assistance system operation, 3) determine the relationship between school administrators’ roles and the student assistance system operation, and 4) identify school administrators’ roles that affected the student assistance system operation. The sample consisted of 317 school administrators and teachers working under Chachoengsao Primary Educational Service Area Office 1 in the 2024 academic year. The sample size was also determined using Krejcie and Morgan’s table and selected through multi-stage sampling. The research instrument for data collection was a set of 5-rating scale questionnaires, with the reliability of .98. The statistics used for data analysis included frequency, percentage, mean, standard deviation, Pearson’s product–moment correlation coefficient, and Stepwise multiple regression analysis. The research findings revealed that 1) school administrators’ roles were rated overall at a high level, ranking by mean scores from high to low: Leadership, interpersonal relationship, supervision, monitoring, and evaluation, and resources allocation; 2) The student assistance system operation was overall at the highest level, ranking by mean scores from high to low: Promotion of student development, prevention and intervention for student problems, individual student profiling, student screening, and referral services for students; 3) The relationship between school administrators’ roles and the student assistance system operation was at a high positive correlation ( =.760), with the .01 level of significance; and 4) school administrators’ roles affecting the student assistance system operation comprised leadership, resource allocation, interpersonal relationship, and supervision, monitoring and evaluation, could predict the student assistance system operation at 58.40 percent. The predictive equation could be written in the standardized score form as Z'Y = .269Z2 + .229Z4 + .173Z3 + .132Z1